The rectus abdominis tendon insertion to the pubic bone and its clinical implications: A cadaveric study - Tourvas Evangelos A.; Zibis Aristidis H.; Klontzas Michail E.; Karantanas Apostolos H.; Bastian Johannes D.; Tosounidis Theodoros H. (SICOT-J)
Purpose: The primary aim of this study is to determine the rectus abdominis tendon (RAT) insertional anatomy and consequently clarify the extension of secure mobilization of the tendon from the pubic bone in the setting of anterior approaches in pelvic and acetabular reconstruction surgery. Materials and methods: Eleven fresh frozen cadaveric pelvises were dissected by two fellowship-trained orthopaedic trauma surgeons utilizing the anterior intrapelvic approach (AIP). The RAT at the pubic body was dissected, and its footprint on the pubic bone was defined, marked, and measured. Results: Nineteen (19) RAT insertions were analyzed. The average total medial vertical length was 33 mm (range 26–42 mm), and the average total lateral vertical length was 36.5 mm (range 26–46 mm). The total width of the proximal insertion on both sides was measured at an average of 20.42 mm (range 14–24 mm). The average width of the tendon at the transition area between the cranial and caudal areas of the pubic bone was 16.45 mm (range 12–22 mm). The average distal insertion width of the RAT was less than the proximal and middle widths, measuring 10.45 mm (range 8–13 mm). Conclusion: The tendon can be safely mobilized up to an average total medial vertical length of 33 mm (and in no case more than 42 mm) and to an average total lateral vertical length of 36.5 mm (and in no case more than 46 mm). This piece of anatomical information will equip orthopaedic surgeons with a better understanding of the insertional anatomy of the RAT and subsequent safer surgical release when performing anterior approaches to the pelvic ring.